1995
DOI: 10.1002/jms.1190300706
|View full text |Cite
|
Sign up to set email alerts
|

Proton‐transfer reactions within ionized methanol clusters: Mass spectrometric and molecular orbital studies

Abstract: Proton-transfer reactions that proceed within methanol cluster ions were studied using an electron impact time-offlight mass spectrometer. When CH,OH seeded in helium is expanded and ionized by electron impact, the protonated species, (CH,OH),H+, are the predominant cluster ions in the low-mass region. In CH,OD clusters, both (CH,OD),H+ and (CH,OD),D+ ions are observed. The ion abundance ratios, (CH30D),H+/(CH30D),D+, show a tendency to decrease as the methanol concentration increases, which is apparently rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 35 publications
5
25
1
Order By: Relevance
“…Type II is the result of an intracluster reaction in which H in the methyl group of CH 3 OH rearranges onto the O atom. From the energies listed in Table 1, it can be seen that type II is a more stable configuration, which is analogous to the result reported in [11]. Fig.…”
Section: Mass Spectrasupporting
confidence: 84%
“…Type II is the result of an intracluster reaction in which H in the methyl group of CH 3 OH rearranges onto the O atom. From the energies listed in Table 1, it can be seen that type II is a more stable configuration, which is analogous to the result reported in [11]. Fig.…”
Section: Mass Spectrasupporting
confidence: 84%
“…Previous studies of the electron impact ionization of methanol clusters in the gas phase have revealed no detectable parent methanol cluster ions [25,26]. Equally, in their investigation of ion products from a broader range of clusters, Shukla and Stace also observed no parent cluster ions for any of the alcohols studied [24].…”
Section: Discussionmentioning
confidence: 78%
“…Vertical ionization results in ions being produced with considerable excess vibrational energies, which then allow rapid conversion to the protonated species. In the specific case of (MeOH) 2 , ab initio calculations predict that vertical ionization results in a cation with a total energy above that for (MeOH)H + + OMe [26]. The calculations show that the transition state for the process…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Reaction (5) probably proceeds over small clusters of protonated methanol, which have been found to be preferentially formed in methanol-noble gas mixtures by electron impact ionisation. 25 3 18 OD + . After extraction of the ions from the source at 40 keV, they were mass selected, injected into the ring and accelerated to 2.90 MeV (CH 3 OH 2 + ) and 2.53 MeV (CD 3 OD 2 + ) translational energy.…”
Section: Methodsmentioning
confidence: 99%